Preliminary Study of Greywater Treatment through Rotating Biological Contactor - Ashfaq Ahmed Pathan; Rasool Bux Mahar; Kamran Ansari (Mehran University Research Journal of Engineering and Technology, 2011)
The characteristics of the greywater vary from country to country and it depends upon the cultural and social behavior of the respective country. There was a considerable need to characterize and recycle the greywater. In this regard greywater was separated from the black water and analyzed for various physiochemical parameters. Among various greywater recycling treatment technologies, RBC (Rotating Biological Contactor) is more effective treatment technique in reducing COD (Chemical Oxygen Demand) and organic matters from the greywater. But this technology was not applied and tested in Pakistan. There was extensive need to investigate the RBC technology for greywater recycling at small scale before applying at mass scale. To treat the greywater, a single-stage RBC simulator was designed and developed at laboratory scale. An electric motor equipped with gear box to control the rotations of the disks was mounted on the tank. The simulator was run at the rate of 1.7 rpm. The disc area of the RBC was immersed about 40% in the greywater. Water samples were collected at each HRT (Hydraulic Retention Time) and analyzed for the parameters such as pH, conductivity, TDS (Total Dissolved Solids), salinity, BOD5 (Biochemical Oxygen Demand), COD and suspended solids by using standard methods. The results are encouraging with percentage removal of BOD5 and COD being 53 and 60% respectively.